Single‐channel 100 Gbit/s transmission using III–V UTC‐PDs for future IEEE 802.15.3d wireless links in the 300 GHz band. Issue 10 (1st May 2018) - Chinni, V.K.; Latzel, P.; Zégaoui, M.; Coinon, C.; Wallart, X.; Peytavit, E.; Lampin, J.F.; Engenhardt, K.; Szriftgiser, P.; Zaknoune, M.; Ducournau, G.
Abstract : The achievement of single‐channel 100 Gbit/s transmission, using linear unitravelling carrier photodiodes and QAM‐16 modulation format is reported. The wireless link has been done in the indoor case, considering the recent frequency standardised 300 GHz bands.